2020
DOI: 10.1523/jneurosci.2105-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Streaming of Repeated Noise in Primary and Secondary Fields of Auditory Cortex

Abstract: Statistical regularities in natural sounds facilitate the perceptual segregation of auditory sources, or streams. Repetition is one cue that drives stream segregation in humans, but the neural basis of this perceptual phenomenon remains unknown. We demonstrated a similar perceptual ability in animals by training ferrets of both sexes to detect a stream of repeating noise samples (foreground) embedded in a stream of random samples (background). During passive listening, we recorded neural activity in primary au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
(115 reference statements)
1
4
0
Order By: Relevance
“…A1 sites detected temporally coherent frequency elements that had no simple mathematical relationship to each other (Figures 3C-3E, 4A, and 4E), unlike previous work that identified A1 responses to harmonically related elements (Feng and Wang, 2017). These results accord with recent findings showing that perceptual organization depends on the primary auditory cortex for the segregation of repeated noise stimuli (Saderi et al, 2020) and synchronous tone sequences (Lu et al, 2017). In addition, dynamic causal modeling has demonstrated disinhibition of the primary core during the presentation of auditory figures .…”
Section: Discussionsupporting
confidence: 88%
“…A1 sites detected temporally coherent frequency elements that had no simple mathematical relationship to each other (Figures 3C-3E, 4A, and 4E), unlike previous work that identified A1 responses to harmonically related elements (Feng and Wang, 2017). These results accord with recent findings showing that perceptual organization depends on the primary auditory cortex for the segregation of repeated noise stimuli (Saderi et al, 2020) and synchronous tone sequences (Lu et al, 2017). In addition, dynamic causal modeling has demonstrated disinhibition of the primary core during the presentation of auditory figures .…”
Section: Discussionsupporting
confidence: 88%
“…2019 a , b ; Saderi et al . 2020). Electrophysiological and fMRI studies suggest a role for repetition suppression/adaptation to repeating stimuli in support of image sharpening and perceptual priming (Gross et al .…”
Section: Discussionmentioning
confidence: 99%
“…Prediction error is a mechanism to strengthen the internal representation of less temporally distinct/ambiguous stimuli which may lead to generation of a better prediction upon the next repetition (Rao & Ballard, 1999). Studies have suggested increased use of predictive coding in order to cope with less distinct stimuli or ageing accompanied by a less temporally distinct/lower signal-to-noise ratio (Heinemann et al 2011;Peelle & Wingfield, 2016;Presacco et al 2019;Price et al 2019;Bidelman et al 2019a,b;Saderi et al 2020). Electrophysiological and fMRI studies suggest a role for repetition suppression/adaptation to repeating stimuli in support of image sharpening and perceptual priming (Gross et al 1967;Dolan et al 1997;James et al 2000;Grill-Spector et al 2006;Näätänen et al 2007).…”
Section: Temporal Distinction and Top-down Resource Usagementioning
confidence: 99%
“…Indeed, neurons in non-primary ACx exhibit greater invariance in encoding acoustically distorted communicative signals compared to neurons in primary ACx ( Carruthers et al, 2013 , 2015 ). Similarly, dual recordings from primary and secondary ACx in ferrets trained to detect streams of repeated noise samples embedded in a stream of random background samples found that stream-specific gain enhancement was stronger in secondary cortical areas compared to primary ACx ( Saderi et al, 2020 ). Importantly, categorical sound representations in higher-order cortical regions are often behaviorally-gated, adaptively assuming different states or filter properties depending upon the demands of the ongoing task.…”
Section: Top-down Contributions To Auditory Scene Analysismentioning
confidence: 99%